2018
DOI: 10.1007/s00234-018-2127-9
|View full text |Cite
|
Sign up to set email alerts
|

Black bone MRI with 3D reconstruction for the detection of skull fractures in children with suspected abusive head trauma

Abstract: Dear Neuroradiology Editors, I am pleased to submit for review on behalf of myself and my co-authors the following original research paper titled "Black Bone MRI with 3D reconstruction for the Detection of Skull Fractures in Children with Suspected Abusive Head Trauma." Black bone MRI sequences are newer MRI sequences which have been developed for imaging of the bone with MRI. The purpose for this original research was to compare a black bone MRI sequence to head CT for detection of skull fractures in pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 23 publications
2
56
0
Order By: Relevance
“…Non-accidental injury in the paediatric population offers similar challenges with a need for comprehensive and ideally non-ionising imaging. The potential for BB and the ZTE equivalent, PETRA, techniques in the diagnosis of craniosynostosis and skull fractures has been demonstrated [3,8]. The demonstrated benefits of a combined ZTE+ BB or ZTE+FIESTA-C segmentation algorithm would be of clear benefit in these patient groups, albeit with the requirement for further confirmation of their accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-accidental injury in the paediatric population offers similar challenges with a need for comprehensive and ideally non-ionising imaging. The potential for BB and the ZTE equivalent, PETRA, techniques in the diagnosis of craniosynostosis and skull fractures has been demonstrated [3,8]. The demonstrated benefits of a combined ZTE+ BB or ZTE+FIESTA-C segmentation algorithm would be of clear benefit in these patient groups, albeit with the requirement for further confirmation of their accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The main benefit of this GRE-based technique is that it can be implemented on all MRI systems irrespective of vendor or field strength. Previous attempts with GRE-BB to produce 3D rendered imaging of the craniofacial skeleton have shown considerable promise, but remain limited by time-intensive segmentation techniques [2][3][4][5][6][7][8]. Recent developments in an automated segmentation algorithm have brought these techniques significantly closer to routine clinical practice [9].…”
Section: Introductionmentioning
confidence: 99%
“…The ‘Black‐bone’ MRI sequence has been used previously in the craniofacial skeleton, to offer a non‐ionizing alternative to CT in children with skull abnormalities 5 ,. 6 , 21–24 Robinson et al 25 . found that foetal ‘Black‐bone’ MRI could be used in the assessment of spinal abnormalities, therefore reducing the risks of ionizing radiation to the mother and the foetus.…”
Section: Discussionmentioning
confidence: 99%
“…CT) [13,14]. Black bone MRI sequences aim to suppress fat and water simultaneously to create uniform signal for soft tissues, thus differentiating it from bone tissue with high-spatial resolution for applications in the head and neck such as craniosynostosis, skull trauma, or 3D-printing [15][16][17][18]. However, while Eley et al showed that black bone MRI has comparable spatial performance for CT measurement across the image, the feasibility and utility of using black bone MR images for quantitative cortical assessment for the mandible has yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…CT) [13,14]. Black bone MRI sequences aim to suppress fat and water simultaneously to create uniform signal for soft tissues, thus differentiating it from bone tissue with high-spatial resolution for applications in the head and neck such as craniosynostosis, skull trauma, or 3D-printing [1518]. However, while Eley et al .…”
Section: Introductionmentioning
confidence: 99%